Correction of miscarriages of justice in New Zealand and England - Birdling, M; Malcolm Birdling (2012)
This thesis sets out to provide a deep analysis of the mechanisms for review of convictions in New Zealand and England after initial appeal rights are exhausted, and to identify the key areas of similarity and difference between these systems, the reasons for these differences, and their implications. The appeal systems in each jurisdiction are briefly examined, alongside the pressures and restrictions on their functioning. Particular attention is paid to the options for appeal out of time, and for revisiting appeal decisions if new material comes to light. The main discussion is of the specialist procedures for review of suspect convictions in each jurisdiction: the Royal Prerogative of Mercy process carried out by the New Zealand Ministry of Justice and the work of the English Criminal Cases Review Commission. This discussion presents the results of empirical research carried out by the author utilising the files of each of these bodies. It investigates the legal context in which each body functions, and provides an account of how each body functions in practice, by examining the circumstances in which each body will contemplate referring a matter back to an appeal court and the means by which a determination is made as to whether to do so in an individual case. In addition it examines the various factors (legal and non-legal) which impact on their work. Finally, the key features of the two systems are contrasted, with a discussion of the areas of similarity and difference, as well as the possible implications of these, in particular for reform of the New Zealand processes.